Biogas as a way to attract renewable energy - Kardasz, Piotr (Видавництво Львівської політехніки, 2013)
The subject of the following article is biogas plant, which is an installation for the production of biogas. Biogas can be used to produce electricity, heat and fuels. Produced by the fermentation of biomass materials that can be used (mainly waste from agricultural, animal and food industry), sediments, sewage treatment and municipal waste lying in landfills. Depending on the type of feedstock used in biogas technology may be different, but the basic elements of the system of administration of biomass digester and gas storage tanks and waste resulting digestate. Biogas sector in Poland is still not very large, but rapidly growing.
Keywords: biogas plant; biomass; biogas; renewable energy; waste; anaerobic digestion